Application of seismic full waveform inversion to monitor CO2 injection: Modelling and a real data example from the Ketzin site, Germany - Zhang, F.; Juhlin, Christopher; Ivandic, M.; Lüth, S. (2013)
Seismic monitoring of an injected carbon dioxide (CO2) distribution at depth is an important issue in the geological storage of CO2. To help monitor changes in the subsurface during CO2 injection a series of 2D seismic surveys were acquired within the framework of the CO2SINK and CO2MAN projects at Ketzin, Germany at different stages of the injection process. Here we investigate using seismic full waveform inversion as a qualitative tool for time-lapse seismic monitoring given the constraints of the limited maximum offsets of the 2D seismic data. Prior to applying the inversion to the real data we first made a number of benchmark tests on synthetic data using a similar geometry as in the real data. Results from the synthetic benchmark tests show that it is difficult to recover the true value of the velocity anomaly due to the injection but that it is possible to qualitatively locate the distribution of the injected CO2. After the synthetic studies, we applied seismic full waveform inversion on the real time-lapse data from the Ketzin site along with conventional time-lapse processing. Both methods show a similar qualitative distribution of the injected CO2 and agree well with expectations based upon more extensive 3D time-lapse monitoring in the area.